IMPLEMENTASI NILAI-NILAI ISLAM UNTUK MENINGKATKAN AKHLAK DAN MORAL PESERTA DIDIK DI TADIKA NADI ILMU - Duwi Agutin Sitorus; Munawir Pasaribu (Ilmuna: Jurnal Studi Pendidikan Agama Islam, 2026)
Early childhood education plays a strategic role in shaping the character and morals of students through the instillation of Islamic values from an early age. This study aims to describe the implementation of Islamic values in early childhood education and analyze the role of teachers and parents in shaping the character and morals of students at Tadika Nadi Ilmu. This study uses a qualitative approach with a descriptive method. Data collection techniques were carried out through observation, interviews, and documentation of teachers, students, and parents. The results of the study show that the implementation of Islamic values at Tadika Nadi Ilmu is carried out through the exemplary behavior of teachers, the habit of worship, integrated learning, and the creation of an Islamic environment. Teachers act as role models and agents of change in instilling Islamic moral values, while parents play a role in reinforcing the habit of Islamic values in the family environment. The consistent and integrated implementation of Islamic values has a positive impact on the formation of students' character and morals, which is reflected in their religious attitudes, politeness, discipline, responsibility, and social awareness. This study confirms that synergy between educational institutions and families is a key factor in the success of Islamic character education in early childhood.